Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12665-017-6868-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential damage in the semi-confined Munazio Ireneo cubicle in Cagliari (Sardinia): a correlation between damage and microclimate

Abstract: The Early Christian Munazio Ireneo cubicle in Cagliari (Sardinia) is carved into the rock and is one of the rare monuments of Sardinia belonging to Early Christian Age. It is 166 cm under the planking level and is a semi-confined chamber in which a gate allows exchange with the outside. In 1888, when it was discovered, it was completely painted, but over the years, it suffered a serious damage and all the paintings are nearly disappeared. Now the site shows a high moisture and a differential damage characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These values can be explained with the time of outdoor exposition (1876 RR, 1890 AV, and 1900 FGM their years of built) and even more by microclimatic conditions. Previous studies showed that the most damaged marble pieces in the cemetery of Cagliari were all characterized by low values of solar radiation, high humidity and a reduced thermoforesis, favoring sulfatation and weathering along with the surfaces' colonization [32,33,67,68]. Indeed, the nearby and dense vegetation, in addition to the low exposition to the dominant winds (Libeccio and Scirocco from south and Mistral from north-west), favored the stagnation of marine air and its penetration into damaged stones.…”
Section: Marble Deterioration Degree Selects the Resident Fungal Comm...mentioning
confidence: 99%
“…These values can be explained with the time of outdoor exposition (1876 RR, 1890 AV, and 1900 FGM their years of built) and even more by microclimatic conditions. Previous studies showed that the most damaged marble pieces in the cemetery of Cagliari were all characterized by low values of solar radiation, high humidity and a reduced thermoforesis, favoring sulfatation and weathering along with the surfaces' colonization [32,33,67,68]. Indeed, the nearby and dense vegetation, in addition to the low exposition to the dominant winds (Libeccio and Scirocco from south and Mistral from north-west), favored the stagnation of marine air and its penetration into damaged stones.…”
Section: Marble Deterioration Degree Selects the Resident Fungal Comm...mentioning
confidence: 99%
“…Climate change and its consequences are becoming mandatory issues to be tackled by international and local authorities in charge of risk assessment and responsible for taking actions to mitigate their effects: this is true not only with regard to the environment, but also with respect to cultural heritage. Indeed, the combined action of natural weathering agents (e.g., rainfall, fog, snow, or salts) and atmospheric pollutants derived from anthropogenic activity drastically changes the material-atmosphere interface, causing the loss of the surface material and, consequently, the loss of its aesthetic quality [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%